Kelimpahan Fitoplankton sebagai Bioindikator Lingkungan Perairan di Sungai Uram, Kabupaten Lebong - Meliya Wati; Novia Duya; Gress Pinesta; Putri Lisya Anggraini; Khonita R. Diani; Darmi; Rizwar (Jurnal Biosilampari : Jurnal Biologi, 2026)
Phytoplankton are primary producers that respond rapidly to environmental changes and therefore have considerable potential as bioindicators of aquatic ecosystem conditions. This study aimed to analyze the abundance and community structure of phytoplankton and evaluate their ecological significance as bioindicators in the Uram River, Lebong Regency, Bengkulu Province. Sampling was conducted at four stations representing different habitat characteristics along the river continuum, including upstream, dam-influenced, settlement-associated, and downstream segments. Phytoplankton samples were collected using a plankton net and identified microscopically. Community analysis included abundance, Shannon-Wiener diversity, evenness, and dominance. A total of 52 phytoplankton species belonging to eight classes were identified, with Bacillariophyta as the dominant group, contributing 46.2% of the total species composition. The highest abundance was recorded at Station I (2,316.6 ind/L), while the highest diversity index was observed at Station III (H' = 3.380). High evenness values (0.855–0.898) and low dominance values (0.072–0.097) indicated a relatively stable community structure. Variations in phytoplankton composition among stations reflected differences in habitat conditions influenced by flow velocity, substrate characteristics, riparian vegetation, and human activities. These findings demonstrate that phytoplankton are effective bioindicators for assessing ecological conditions and provide baseline information for aquatic resource management and biomonitoring programs in the Uram River.